Conceptual design of a simulation model for bulk material transport by pipe conveyor - Bobinics, Bohdana; Marasova, Daniela (Bulletin of the Polish Academy of Sciences Technical Sciences, 2026)
Pipe conveyors provide an environmentally advantageous alternative to conventional belt conveyors for bulk material transport. While FEM, DEM, and CFD methods have led to significant advancements in the analysis of belt mechanics and particle dynamics, published pipe conveyor simulations typically cover narrow parameter ranges and offer limited insight into how operating parameters jointly influence system performance under realistic, variable loading conditions. This article presents a simulation model for bulk material transport by pipe conveyor in Tecnomatix Plant Simulation, using a mathematical capacity model implemented in SimTalk 2.0. A stochastic feeding model based on a uniform random distribution approximates the real variability of material loading. A parametric study of 27 experiments in five series evaluates the influence of belt speed (0.8–4.0 ms−1 ), filling coefficient (0.44–0.80), conveyor length (100–1000 m), feeding deviation (1–100%), and inclination angle (0° –15° ) on nominal and actual throughput. Belt speed and filling coefficient affect throughput proportionally, while conveyor length and inclination angle have no measurable influence. The proposed model provides a flexible digital tool for analyzing the material flow dynamics of pipe conveyors and supports system design.